2017
DOI: 10.4081/jphia.2017.704
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section in a primary health facility in Ghana: Clinical indications and feto-maternal outcomes

Abstract: There is great concern about the increasing rise in the rate of caesarean section in both developed and developing countries. This study was to ascertain the prevalence and compare outcomes of elective and emergency caesarean sections among women who deliver at the University of Cape Coast Hospital, Ghana. This retrospective study reviewed records of 645 women who delivered through caesarean sections during the period of January 2014 and December 2015. The prevalence of caesarean section was 26.9%. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 11 publications
7
20
2
Order By: Relevance
“…The study from Ghana stated that the lack of assisted vaginal delivery and proper labour monitoring facilities made the mother less confident in choosing normal birth. 49 Whereas physician incompetency to handle complicated labour was suspected in one study from China. 42 A study from Nigeria documented that when women prefer CD, obstetricians are less likely to oppose this.…”
Section: Systematic Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study from Ghana stated that the lack of assisted vaginal delivery and proper labour monitoring facilities made the mother less confident in choosing normal birth. 49 Whereas physician incompetency to handle complicated labour was suspected in one study from China. 42 A study from Nigeria documented that when women prefer CD, obstetricians are less likely to oppose this.…”
Section: Systematic Review Findingsmentioning
confidence: 99%
“…Out of ten available safeguards, the lowest count achieved was six, [50][51][52] and the highest count was 10. 40,41,44,53 Only a few of the studies mentioned the representativeness for the national population, 25,27,40,41,43,44,53,54 and some did not discuss representativeness against the target population, 26,28,45,46,[48][49][50][51][52][55][56][57][58][59][60] which jeopardised the external validity. The outcome definition for CDMR did not match in four articles, where previous CD was included as a reason for CDMR.…”
Section: Study Qualitymentioning
confidence: 99%
“…Although there have been some studies on CD in Ghana, some of them focused on socioeconomic and demographic factors associated with CD in southern Ghana [14], preference of Ghanaian women for vaginal or CD postpartum [21], validating women's self-report of emergency CD [18], vaginal birth after a previous CS [22] and clinical indications and feto-maternal outcomes and predictors of CD in Northern Ghana [23]. As far as we know, none of these studies have used a nationally representative sample to assess prevalence and the factors associated with CD among childbearing women in Ghana despite the country recording an overall rate of 16% [24], above the threshold given by WHO.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted at the University of Cape Coast Teaching Hospital found a C/S rate of 26.9%. 63 Though there is inconsistency in the rate of C/S, it is clear the rates are relatively high. Moving forward there is, therefore, the need to do case reviews of C/S conducted in different hospitals to inform policy.…”
Section: Discussionmentioning
confidence: 99%